Enhancing Learning Experiences and Outcomes Using Virtual Media for Children with Autism Spectrum Disorders - Kamid; Anwar, Khairul (Mathematics Education Journal, 2025)
This study aimed to develop a Virtual Learning Environment (VLE) for mathematics learning tailored to children with Autism Spectrum Disorders (ASD) at a special needs school in Jambi, utilizing the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model. It focused on enhancing the learning experiences and outcomes for ASD students in a specialized education setting. In the Analysis phase, the needs and challenges of ASD students in learning mathematics were identified through observations, interviews, and literature review. The Design phase involved creating a detailed blueprint for the VLE, emphasizing interactive and user-friendly features. During the Development phase, the VLE was developed incorporating multimedia elements to engage students effectively. The Implementation phase included deploying the VLE in the classroom and training teachers and students to use the system. The Evaluation phase assessed the VLE's effectiveness through metrics such as visual, verbal, auditory, writing, motor, and emotional activities over four meetings. Results showed consistent improvements in all activities, particularly visual, auditory, writing, and motor activities, demonstrating significant enhancements in student engagement and understanding of mathematical concepts. This research underscores the importance of a structured development process and the positive impact of technology-enhanced learning environments on students with ASD.